Potensial Mineral Kasiterit Pada Tailing Penambangan Timah Daerah Parit Tiga Kabupaten Bangka Selatan - Rezky Dwi Aditya; Irvani Irvani; Janiar Pitulima (MINERAL, 2022)
Unconventional tin mining in Parit Tiga Village, Toboali District, South Bangka Regency is one of the mining sites that is rampantly carried out by the community. The problems that arise from the activities carried out by the community indicate that tin minerals in that location still have the potential to be mined at the conventional mining scale, this condition makes researchers want to study how much potential Sn levels are still contained even though the location is in the form of tailings. Data collection was 16 points at the first tailings location with an area of 160.000 m2 and 15 points at the second tailings location with an area of 150.000 m2. The samples were taken regularly with a distance between samples of 100 meters with a depth of 1,5 meters. Tailings samples were then tested using a microscope overview analysis method to obtain cassiterite levels. The results showed that the study area had 201.15 tons of Cassiterite potential at the first location and 300 tons at the second location to be studied further in terms of its economics.